A high-rate aqueous zinc ion battery electrolyte and preparation method thereof

By using cations with larger ion radius and anions involved in zinc ion solvation as electrolyte additives in aqueous zinc ion batteries, the dendrite growth and hydrogen evolution problems of AZIBs negative electrodes are solved, and high-rate performance and long cycle life are improved .

CN118136982BActive Publication Date: 2025-02-11JIANGSU UNIV +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202410491537.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-23
Publication Date
2025-02-11
Estimated Expiration
2044-04-23

AI Technical Summary

Technical Problem

The negative electrode of the aqueous zinc ion battery (AZIBs) faces dendritic growth, accumulation, polarization, zinc dissolution and precipitation, interface stability and hydrogen evolution, which limits its practical application.

Method used

Electrolyte additives containing cations with a larger ion radius and anions that can participate in the solvation process of zinc ion, so as to improve the uniformity of zinc ion deposition by inhibiting dendrite growth and hydrogen evolution reaction.

Benefits of technology

It effectively improves the rate performance and cycle life of aqueous zinc ion batteries, extends the service life of the battery, and improves the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118136982B_ABST
    Figure CN118136982B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of aqueous zinc ion batteries, and in particular to a high-rate aqueous zinc ion battery electrolyte and a preparation method thereof, wherein the electrolyte comprises a deionized water solvent, a zinc salt and an electrolyte additive. The additive in the present invention contains cations with a larger ionic radius and anions that can participate in the solvation process of zinc ions. Such cations can be gathered at the dendrite tip during zinc deposition, thereby inhibiting dendrite growth and the irreversible hydrogen evolution reaction of hydrated zinc ions, and improving the reversibility of zinc ion deposition. At the same time, the anions and hydrated zinc ions have higher adsorption energy, and can be used as better leaving groups in zinc ion deposition, thereby reducing the reaction energy barrier of hydrated zinc ions dehydration, reducing zinc nucleation sites, assisting zinc ions in uniform deposition, and overall improving the rate performance and cycle life of aqueous zinc ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aqueous zinc ion batteries, and in particular to a high-rate aqueous zinc ion battery electrolyte and a preparation method thereof. Background Art

[0002] Aqueous zinc-ion batteries (AZIBs) have broad application prospects in multivalent metal-ion batteries due to their inherent safety, low cost and stability, and have good potential in sustainable energy storage systems and large-scale applications, while also making up for the dilemma of lithium / sodium-ion batteries. However, the anode of AZIBs faces serious problems of dendrite growth, accumulation, polarization, zinc dissolution and precipitation, interface stability and hydrogen evolution, which limit the practical application of AZIBs.

[0003] At present, the use of electrolyte additives to optimize the stability of zinc-ion batteries has been widely studied. Among the reported zinc-ion battery electrolyte additives, CN202311520136.0 discloses a zinc-ion battery electrolyte containing fluorescent quantum dots. By adding nitrogen-oxygen-modified fluorescent quantum dot additives to the electrolyte, zinc ions are adsorbed, the internal resistance of the battery is reduced, and the transfer rate of zinc ions is increased, thereby improving the discharge performance of the battery. However, its battery life is less than 2 mA / cm 2 CN202311262111.5 discloses that inorganic molecule rubidium iodide is used as an additive for zinc ion batteries. The introduction of iodine ions effectively increases the cycle life of zinc ion batteries. However, there is a serious voltage polarization problem in the system, which deteriorates the high rate performance of zinc ion batteries.

[0004] At the same time, organic molecules can be used to improve the deposition and detachment process of aqueous zinc ion batteries due to their stability, adjustable functional groups and polar structures. CN202310967837.2 uses imidazole and its derivatives as zinc ion battery electrolyte additives, and utilizes the proton binding ability and electrostatic adsorption of organic molecules to remove zinc dendrites and optimize the zinc electrode surface. CN202410095047.4 The latter utilizes the high polarity of acyl ester organic molecules to participate in the solvation process of zinc ions and induce the growth of zinc (002) crystal faces. CN117673506A uses propane sulfonic acid pyridinium salt as a zinc ion battery electrolyte additive to improve the cycle life at low rates. However, larger organic molecules are not conducive to the migration of zinc ions on the surface of zinc metal, which increases the voltage hysteresis problem during the deposition and stripping process, thereby fundamentally increasing the burden of battery operation. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art and propose a high-rate aqueous zinc ion battery electrolyte and a preparation method thereof. By adopting additives containing cations with larger ionic radius and anions that can participate in the zinc ion solvation process, the rate performance and cycle life of the aqueous zinc ion battery can be effectively improved as a whole.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A high-rate aqueous zinc ion battery electrolyte comprises a deionized water solvent, a zinc salt and an electrolyte additive.

[0008] Preferably, the zinc salt is any one or more of zinc sulfate (ZnSO4), zinc sulfate hydrate, zinc acetate, zinc acetate hydrate, zinc nitrate, zinc nitrate hydrate, zinc chloride, zinc chloride hydrate, zinc bromide, zinc bromide hydrate, zinc trifluoromethanesulfonate, zinc trifluoromethanesulfonate hydrate, zinc iodide and zinc iodide hydrate.

[0009] Preferably, the electrolyte additive is any one or more of cesium iodide (CsI), cesium bromide (CsBr), tetrabutylammonium iodide (TBAI), tetrabutylammonium bromide (TBAB), strontium bromide (SrBr2) and strontium iodide (SrI2).

[0010] Preferably, the concentration of the zinc salt is 0.8 mol / L-3 mol / L, the amount of the electrolyte additive added is 0.02 mol / L-2 mol / L, and the obtained electrolyte is acidic or neutral.

[0011] The present invention also provides a method for preparing a high-rate aqueous zinc ion battery electrolyte, comprising the following steps:

[0012] Step S1, mixing zinc salt and deionized water solvent in an appropriate proportion, and continuously stirring with a magnetic stirrer at room temperature until the solution is completely clear and transparent without precipitation, to obtain a mixed solution;

[0013] Step S2, adding the electrolyte additive to the mixed solution of step S1, and continuously stirring under a magnetic stirrer until the electrolyte additive is completely dissolved, to obtain a high-rate aqueous zinc ion battery electrolyte.

[0014] Another object of the present invention is to provide a high-rate aqueous zinc ion battery, comprising a positive electrode, a negative electrode, a separator and the above-mentioned high-rate aqueous zinc ion battery electrolyte.

[0015] Preferably, the negative electrode is zinc metal or zinc alloy.

[0016] Preferably, the operating current density of the battery is 0.1 mA / cm 2 ~50mA / cm2 .

[0017] Preferably, the battery is a Zn||Zn symmetrical battery composed of a commercial 0.1 mm thick zinc foil, a glass fiber separator and an aqueous zinc ion battery electrolyte.

[0018] Preferably, the battery is a Zn||Cu half-cell composed of a commercial zinc foil with a thickness of 100 um, a commercial copper foil current collector, a glass fiber separator and an aqueous zinc ion battery electrolyte.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The high-rate aqueous zinc ion battery electrolyte prepared by the present invention contains cations with larger ionic radius and anions that can be complexed with hydrated zinc ions in its additives; such cations gather at the dendrite tip during zinc deposition, thereby inhibiting dendrite growth and irreversible hydrogen evolution reaction of hydrated zinc ions. At the same time, the anions have higher adsorption energy with hydrated zinc ions, and as a better leaving group in zinc ion deposition, they can reduce the reaction energy barrier of dehydration of hydrated zinc ions, reduce the nucleation sites of zinc, and assist in uniform deposition of zinc ions.

[0021] 2. The present invention can obtain very good stability and further improve the safety of the battery by adding high-efficiency additives without changing the basic physical properties of the aqueous zinc ion battery electrolyte, such as viscosity and pH value, and has no effect on the typical assembly process of the battery. The additives used in the high-rate aqueous zinc ion battery electrolyte of the present invention are moderately priced, the synthesis process is mature and green and environmentally friendly, and only a trace amount of addition is required to improve the electrochemical performance of the zinc negative electrode. Symmetrical batteries using the high-rate aqueous zinc ion battery electrolyte of the present invention can achieve a high stability at 20 mA / cm 2 The current density was cycled for more than 1000 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the nucleation overpotential of the Zn||Cu half-cell of the 2 mol / L ZnSO4 electrolyte prepared by the present invention and the 2 mol / L ZnSO4 electrolyte with 5 mmol / L, 50 mmol / L and 100 mmol / L CsI added thereto respectively;

[0023] Figure 2 The first three charge-discharge curves of the Zn||Cu half-cell of the 2mol / L ZnSO4 electrolyte prepared by the present invention and the 2mol / L ZnSO4 electrolyte added with 100mmol / L CsI and 100mmol / L sodium iodide (NaI) respectively;

[0024] Figure 3The charge-discharge curves of the Zn||Cu half-cell of the 2mol / L ZnSO4 electrolyte prepared by the present invention and the 2mol / L ZnSO4 electrolyte added with 100mmol / L CsI and 100mmol / LNaI, respectively, from the 4th to the 54th cycles;

[0025] Figure 4 The Zn||Cu half-cell cycle life curves of the 2mol / L ZnSO4 electrolyte prepared by the present invention and the 2mol / L ZnSO4 electrolyte with 100mmol / L CsI added;

[0026] Figure 5 A comparison chart of the Tafel electrochemical corrosion current test of Zn||Zn on a battery of a 2mol / L ZnSO4 electrolyte prepared by the present invention and a 2mol / L ZnSO4 electrolyte with 100mmol / L CsI added;

[0027] Figure 6 The high current density (20 mA / cm2) of the Zn||Zn symmetric battery prepared by the present invention is 2 mol / L ZnSO4 electrolyte and 2 mol / L ZnSO4 electrolyte with 100 mmol / L CsI added. 2 ) Schematic diagram of cycle performance. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings, so that those skilled in the art can better understand the advantages and features of the present invention, thereby making a clearer definition of the protection scope of the present invention. The embodiments described in the present invention are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work belong to the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.

[0029] Example 1

[0030] Preparation of electrolyte: Weigh 11.5 g zinc sulfate heptahydrate (ZnSO4·7H2O) and dissolve it in 15 g deionized water to prepare a 2 mol / L ZnSO4 solution for use. Take 5 ml of the above ZnSO4 solution and add 64.85 mg CsI to dissolve, mix well, and obtain a colorless clear electrolyte with a CsI concentration of 50 mmol / L (referred to as 50CsI).

[0031] Battery assembly: Take a 0.1 mm thick commercial zinc foil and cut it The zinc electrode sheet is cleaned with anhydrous ethanol and dried for later use; the glass fiber diaphragm is cut into The disc is ready for use; take the commercial copper foil current collector and cut it The copper current collector disc is cleaned and dried with anhydrous ethanol for later use. The zinc electrode sheet, diaphragm, and zinc electrode sheet are stacked in order and placed in a 2032-type battery shell, and 60μL~80μL of electrolyte is added to wet the inside to assemble into a 2032-type Zn||Zn symmetrical button battery, recorded as Zn||Zn-50CsI. The copper current collector, diaphragm, and zinc electrode sheet are stacked in order and placed in a 2032-type battery shell, and 60μL~80μL of electrolyte is added to wet the inside to assemble into a 2032-type Zn||Cu button half-cell, recorded as Zn||Cu-50CsI.

[0032] Battery test: The test method for Zn||Zn symmetrical battery is: at 20mA / cm 2 The current density is constant current charge and discharge to 1 mAh / cm 2 The test method of Zn||Cu half-cell is: at 1mA / cm 2 After 1h of constant current discharge at a current density, the battery was charged to 0.4V at the same current density, and the cycle was repeated. In addition, the Zn||Zn symmetric battery was subjected to Tafel corrosion current test with parameters of -0.25V to 0.25V and a scan rate of 1mV / s.

[0033] Example 2

[0034] This example is similar to Example 1 in that the concentration of CsI in the electrolyte is 100 mmol / L, and the remaining steps are the same as those in Example 1 to obtain a colorless clear electrolyte (referred to as 100CsI). At the same time, button cells are assembled in the manner of Example 1, wherein the Zn||Zn symmetrical cell and the Zn||Cu half-cell are respectively referred to as Zn||Zn-100CsI and Zn||Cu-100CsI.

[0035] Example 3

[0036] This example is similar to Example 1 in parallel experiments, using CsBr as an electrolyte additive at a concentration of 500 mmol / L, and the remaining steps are the same as Example 1 to obtain a uniform electrolyte (referred to as 500CsBr). At the same time, button cells are assembled in the manner of Example 1, wherein the Zn||Zn symmetrical cell and the Zn||Cu half-cell are respectively referred to as Zn||Zn-500CsBr and Zn||Cu-500CsBr.

[0037] Example 4

[0038] This example is similar to Example 3 in parallel experiments, the concentration of CsBr in the electrolyte is 100mmol / L, and the remaining steps are the same as Example 3 to obtain a uniform electrolyte (referred to as 100CsBr). At the same time, button cells are assembled in the manner of Example 1, wherein the Zn||Zn symmetrical cell and the Zn||Cu half-cell are respectively referred to as Zn||Zn-100CsBr and Zn||Cu-100CsBr.

[0039] Example 5

[0040] This example is similar to Example 3 in parallel experiments, the concentration of CsBr in the electrolyte is 200mmol / L, and the remaining steps are the same as Example 1 to obtain a uniform electrolyte (referred to as 200CsBr). At the same time, button cells are assembled in the manner of Example 3, wherein the Zn||Zn symmetrical cell and the Zn||Cu half-cell are respectively referred to as Zn||Zn-200CsBr and Zn||Cu-200CsBr.

[0041] Comparative Example 1

[0042] In this comparative example, no additives were added, the electrolyte was only 2 mol / L ZnSO4 solution, and the remaining operation steps were the same as those in Example 1, which was recorded as Blank. At the same time, button cells were assembled and tested in the same manner as in Example 1, where the Zn||Zn symmetrical cell and the Zn||Cu half-cell were recorded as Zn||Zn-Blank and Zn||Cu-Blank, respectively.

[0043] Comparative Example 2

[0044] In this comparative example, 6.49 mg CsI was weighed with a high precision balance and added to 5 ml of 2 mol / L ZnSO4 solution to obtain an electrolyte with a CsI concentration of 5 mmol / L, denoted as 5CsI, and the remaining steps were the same as those in Example 1. At the same time, button cells were assembled and tested in the manner of Example 1, wherein the Zn||Zn symmetrical cell and the Zn||Cu half-cell were denoted as Zn||Zn-5CsI and Zn||Cu-5CsI, respectively.

[0045] Comparative Example 3

[0046] In this comparative example, an additive CsCl was used, and 84.04 mg of CsCl (100 mmol / L) was added to 5 ml of a 2 mol / L ZnSO4 solution, and the mixture was uniformly mixed to obtain an electrolyte (referred to as 100CsCl), and the remaining steps were the same as those in Example 1. A button cell was assembled and tested in the same manner as in Example 1, wherein the Zn||Zn symmetrical cell and the Zn||Cu half cell were respectively referred to as Zn||Zn-100CsCl and Zn||Cu-100CsCl.

[0047] Comparative Example 4

[0048] In this comparative example, NaI additive was used, and 74.86 mg of NaI (100 mmol / L) was added to 5 ml of 2 mol / L ZnSO4 solution, and the mixture was uniformly mixed to obtain an electrolyte (referred to as 100 NaI), and the remaining steps were the same as those in Example 1. Meanwhile, button cells were assembled and tested in the same manner as in Example 1, wherein the Zn||Zn symmetrical cell and the Zn||Cu half cell were respectively referred to as Zn||Zn-100NaI and Zn||Cu-100NaI.

[0049] Electrochemical performance testing and data analysis

[0050] The button-type batteries of Zn||Cu-50CsI, Zn||Cu-100CsI, Zn||Cu-Blank, and Zn||Cu-5CsI in Example 1, Example 2, Comparative Example 1, and Comparative Example 2 were tested respectively. The nucleation overpotential of zinc metal on copper foil in the first discharge curve is shown in FIG. Figure 1 As shown, compared with the Blank electrolyte in Comparative Example 1 and the 5CsI electrolyte in Comparative Example 2, the 50CsI electrolyte in Example 1 has a lower nucleation overpotential, so the zinc ions in the 50CsI electrolyte have lower nucleation and growth barriers on the copper foil. Moreover, with the increase of CsI concentration, the nucleation overpotential in 100CsI in Example 2 is further reduced. This result shows that the addition of CsI above a certain concentration can effectively improve the zinc affinity of copper foil.

[0051] The first three charge-discharge curves of Zn||Cu-Blank in Comparative Example 1, Zn||Cu-100NaI in Comparative Example 4, and Zn||Cu-100CsI in Example 1 are as follows: Figure 2 As shown in the figure, it can be seen that the introduction of iodine ions improves the coulombic efficiency of the Zn||Cu battery. At the same time, at around 1.5V, the voltage platform existing in the first three circles of Zn||Cu-Blank disappears in Zn||Cu-100NaI and Zn||Cu-100CsI. This is because iodine ions participate in the dehydration process of hydrated zinc ions, accelerate and assist the deposition of zinc ions, and inhibit the growth of zinc dendrites and the occurrence of hydrogen evolution reaction.

[0052] Depend on Figure 3From the constant current charge-discharge cycle curves of Zn||Cu-Blank, Zn||Cu-100NaI and Zn||Cu-100CsI, it can be seen that after 50 cycles after the first charge and discharge, Zn||Cu-Blank in Comparative Example 1 and Zn||Cu-100NaI in Comparative Example 4 both produced obvious voltage curve fluctuations at around 1.5V, while Zn||Cu-100CsI in Example 1 did not show obvious fluctuations. This is because in the process of zinc ions depositing on zinc metal, cesium ions gather at the tip of the uneven zinc metal surface. Due to their larger ionic radius, they isolate the migrated zinc ions, inhibit the dendrite reaction of zinc ions at the dendrite tip obtaining electrons and depositing as zinc dendrites, and selectively control the flux of zinc ions depositing on dendrite zinc, thereby further reducing the occurrence of hydrogen evolution reaction. The cycle efficiency and cycle life curves of Zn||Cu-Blank and Zn||Cu-100CsI are shown in Figure 2. Figure 4 As shown, the results indicate that the solvated zinc ion structure with the participation of leaving groups can not only improve its coulombic efficiency, but also prolong its cycle life, thereby realizing zinc ion batteries with high rate performance and long cycle performance.

[0053] The first coulombic efficiency and cycle life of Comparative Example 3 and Example 2 are shown in Table 1. In the absence of the leaving group iodine ion, the cesium ion reduces the coulombic efficiency of the Zn||Cu half-cell in the first cycle, and the high-rate cycle life of the Zn||Zn symmetric battery is sharply reduced. This is due to the lack of participation of iodine anions. The selective flux control of zinc ions by cesium ions cannot suppress the hydrogen evolution reaction of highly active water molecules during zinc deposition. Therefore, the use of anions that assist cesium ion deposition is necessary to improve rate performance. The Tafel corrosion current test results of Zn||Zn-Blank and Zn||Zn-100CsI are shown in Figure 1. Figure 5 As shown in the figure, the corrosion current was significantly reduced after adding 100mmol / L CsI. This result further shows that the iodine ions participate in the solvation structure of zinc ions while reducing the dehydration energy barrier and the synergistic effect of the adsorption shielding effect of the cesium ion tip, which reduces the corrosion of the hydrated zinc ions on the zinc negative electrode to a certain extent.

[0054] Table 1: The first coulombic efficiency of the Zn||Cu half-cell and the cycle life of the Zn||Zn battery (20mA / cm 2 )Comparison table

[0055]

[0056] At 20mA / cm 2The current density is constant current charge and discharge to 1 mAh / cm 2 Cyclic test of Zn||Zn-Blank and Zn||Zn-100CsI button batteries, constant current charge and discharge curves are as follows Figure 6 In the high current density cycle test of the symmetric battery, it can be found that the cycle stability and cycle life of the Zn||Zn symmetric battery with the addition of 100mmol / L CsI are significantly increased, and the voltage polarization is significantly reduced.

[0057] The Zn||Zn symmetric battery cycle performance of Comparative Example 1, Example 3, Example 4 and Example 5 was tested in the same way as above, and the results are shown in Table 2. As the bromide ion concentration increases, the bromide ions participate in the desolvation process of more solvated zinc ions, reducing the nucleation energy barrier on the copper foil in the Zn||Cu half-cell and improving the first coulombic efficiency. In addition, compared with iodine ions, the leaving ability and electron accepting ability of bromide ions are weaker, so the effect of auxiliary deposition at low concentrations is not obvious. Zn||Cu-100CsBr and Zn||Cu-200CsBr produce obvious hydrogen evolution platforms after fewer cycles. However, when the bromide ion concentration in the electrolyte reaches 500mmol / L, the appearance time of the hydrogen evolution platform appears in a higher number of cycles, which can be explained that the redox reversibility of Zn||Cu-500CsBr is significantly improved. At the same time, the stability and cycle life of zinc ion batteries are significantly improved. At 20mA / cm 2 At high current density, the cycle life of Zn||Zn-500CsBr is greatly increased compared with Zn||Zn-100CsBr and Zn||Zn-200CsBr, indicating that higher bromide ion concentration has a significant improvement on the deposition and detachment of zinc in zinc ion batteries.

[0058] Table 2: The first coulombic efficiency of the Zn / / Cu half-cell containing 100mmol / L cesium chloride in 2mol / L ZnSO4 electrolyte and 100mmol / L, 200mmol / L, and 500mmol / L CsBr in 2mol / L ZnSO4, the number of cycles generated by the hydrogen evolution platform, and the effect of Zn||Zn on the battery cycle life (20mA / cm 2 )Comparison table

[0059]

[0060] In summary, the additive in the present invention contains cations with larger ionic radius and anions that can participate in the zinc ion solvation process. Such cations can be gathered at the dendrite tip during zinc deposition, thereby inhibiting dendrite growth and irreversible hydrogen evolution reaction of hydrated zinc ions, and improving the reversibility of zinc ion deposition. At the same time, the anions and hydrated zinc ions have higher adsorption energy, and can serve as better leaving groups in zinc ion deposition, reduce the reaction energy barrier of hydrated zinc ions dehydration, reduce zinc nucleation sites, assist zinc ions in uniform deposition, and overall improve the rate performance and cycle life of aqueous zinc ion batteries.

[0061] The description and practice disclosed in the present invention are easy to think and understand for ordinary technicians in the technical field, and several improvements and modifications can be made without departing from the principles of the present invention. Therefore, modifications or improvements made without departing from the spirit of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A high-rate aqueous zinc ion battery electrolyte, characterized in that: The electrolyte comprises a deionized water solvent, a zinc salt and an electrolyte additive; The zinc salt is any one or more of zinc sulfate, zinc sulfate hydrate, zinc acetate, zinc acetate hydrate, zinc nitrate, zinc nitrate hydrate, zinc chloride, zinc chloride hydrate, zinc bromide, zinc bromide hydrate, zinc trifluoromethanesulfonate, zinc trifluoromethanesulfonate hydrate, zinc iodide and zinc iodide hydrate; The electrolyte additive is any one or more of cesium bromide CsBr, strontium bromide SrBr2 and strontium iodide SrI2; The concentration of the zinc salt is 0.8 mol / L-3 mol / L, the amount of the electrolyte additive is 0.02 mol / L-2 mol / L, and the obtained electrolyte is acidic or neutral; The preparation method of the high-rate aqueous zinc ion battery electrolyte comprises the following steps: Step S1, mixing zinc salt and deionized water solvent in an appropriate proportion, and continuously stirring with a magnetic stirrer at room temperature until the solution is completely clear and transparent without precipitation, to obtain a mixed solution; Step S2, adding the electrolyte additive to the mixed solution of step S1, and continuously stirring under a magnetic stirrer until the electrolyte additive is completely dissolved, to obtain a high-rate aqueous zinc ion battery electrolyte.

2. A high rate aqueous zinc ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator and the high-rate aqueous zinc ion battery electrolyte according to claim 1.

3. A high rate aqueous zinc ion battery according to claim 2, characterized in that: The negative electrode is zinc metal or zinc alloy.

4. A high rate aqueous zinc ion battery according to claim 2, characterized in that: The working current density of the battery is 0.1 mA / cm 2 ~50 mA / cm 2 .

Citation Information

Patent Citations

  • Electrolyte additive for aqueous zinc ion secondary battery and battery thereof

    CN116826193A

  • Aqueous zinc ion battery electrolyte containing rubidium iodide additive and application of aqueous zinc ion battery electrolyte

    CN117276694A

  • Aqueous zinc ion battery electrolyte additive, preparation method and application thereof

    CN117613416A

  • Aqueous zinc ion battery composite electrolyte containing acyl acid ester C5-8 alkane chain organic additive with ketone group and ester group as well as preparation method and application of aqueous zinc ion battery composite electrolyte

    CN117613432A

  • Aqueous zinc ion battery electrolyte and preparation method and application thereof

    CN117673506A